Kinematic complexity around NGC 419: resolving the proper motion of the cluster, the Small Magellanic Cloud, and the Magellanic bridge. Issue 2 (11th November 2020) - Massari, Davide; Raso, Silvia; Libralato, Mattia; Bellini, Andrea
ABSTRACT: We present Hubble Space Telescope proper motions in the direction of the star cluster NGC 419 in the Small Magellanic Cloud. Because of the high precision of our measurements, for the first time it is possible to resolve the complex kinematics of the stellar populations located in the field, even along the tangential direction. In fact, the proper motions we measured allow us to separate cluster stars, which move on average with (μ _α δ ^NGC 419, μ _δ ^NGC 419 ) = (+0.878 ± 0.055, −1.246 ± 0.048) mas yr −1, from those of the Small Magellanic Cloud and those belonging to a third kinematic feature that we recognize as part of the Magellanic Bridge. Resolving such a kinematic complexity enables the construction of decontaminated colour–magnitude diagrams, as well as the measurement of the absolute proper motion of the three separate components. Our study therefore sets the first steps towards the possibility of dynamically investigating the Magellanic system by exploiting the resolved kinematics of its stellar clusters.